2017
DOI: 10.1007/s00345-017-2154-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of cytoreductive nephrectomy in synchronous metastatic renal cell carcinoma: a comparative study using inverse probability of treatment weighting

Abstract: IPTW-adjusted analysis of our patient cohort suggests that CN improves OS of patients with synchronous mRCC treated with TT. On the whole, the survival difference appears after 12 months. Specific subgroups may particularly benefit from CN, and these subgroups warrant further investigation in prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
15
1
1
Order By: Relevance
“…Multiple retrospective studies investigated the association between nephrectomy and clinical outcomes among metastatic RCC patients receiving targeted therapy. Most of them supported this population could receive survival benefits from nephrectomy [ 34 37 ]. Using the IMDC database, Heng et al reported metastatic RCC patients who received targeted therapy and cytoreductive nephrectomy had longer OS compared to those on targeted therapy alone (20.6 vs. 9.6 months, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective studies investigated the association between nephrectomy and clinical outcomes among metastatic RCC patients receiving targeted therapy. Most of them supported this population could receive survival benefits from nephrectomy [ 34 37 ]. Using the IMDC database, Heng et al reported metastatic RCC patients who received targeted therapy and cytoreductive nephrectomy had longer OS compared to those on targeted therapy alone (20.6 vs. 9.6 months, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this clinical trial, multiple retrospective studies investigated the association between nephrectomy and clinical outcomes among metastatic RCC patients receiving targeted therapy. Most of them supported metastatic RCC patients treated with targeted therapy could receive survival bene ts from nephrectomy [28][29][30][31]. Based on the IMDC database, Heng et al reported longer OS was associated with metastatic RCC patients who received targeted therapy and cytoreductive nephrectomy than those with targeted therapy alone (20.6 vs. 9.6 months, P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective studies investigated the association between nephrectomy and clinical outcomes among metastatic RCC patients receiving targeted therapy. Most of them supported this population could receive survival bene ts from nephrectomy [34][35][36][37]. Using the IMDC database, Heng et al reported metastatic RCC patients who received targeted therapy and cytoreductive nephrectomy had longer OS compared to those on targeted therapy alone (20.6 vs. 9.6 months, P<0.001).…”
Section: Discussionmentioning
confidence: 99%